1993
DOI: 10.1111/j.1526-4610.1993.hed3305227.x
|View full text |Cite
|
Sign up to set email alerts
|

Headaches During Intracranial Endovascular Procedures: A Possible Model of Vascular Headache

Abstract: We report a series of 11 patients who developed headaches during intracranial endovascular procedures performed for the treatment of arteriovenous malformations (10 cases) or aneurysms (1 case). Headache was precipitated either by balloon inflation (3 cases) or by embolization (8 cases), and had a very constant pattern. In all cases the pain started suddenly, reaching maximum intensity at once. Headache was focal, unilateral, ipsilateral to the occluded artery, nonthrobbing and short-lasting (usually less than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 2 publications
0
43
0
Order By: Relevance
“…This description is similar to previous reports of headache during embolization procedures [7,9,10] and corresponds to the ICHD-II [4] diagnostic criteria for headache attributed to intracranial endovascular procedures (code 6.5.4). Four patients in our series suffered such a headache attack during embolization sessions related to injecting cyanoacrylate or balloon inflation.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…This description is similar to previous reports of headache during embolization procedures [7,9,10] and corresponds to the ICHD-II [4] diagnostic criteria for headache attributed to intracranial endovascular procedures (code 6.5.4). Four patients in our series suffered such a headache attack during embolization sessions related to injecting cyanoacrylate or balloon inflation.…”
Section: Discussionmentioning
confidence: 67%
“…The occurrence of headache during cranial embolization has been attributed to vessel distension occurring with balloon inflation, which stimulates pain receptors in the vessel wall, producing focal areas of referred pain [7,9,10]. Theoretically, it can also occur with contrast injection, if the pressure within the vessel is enough to reach the threshold of mechanical stimulation of pain receptors.…”
Section: Discussionmentioning
confidence: 97%
“…Although headaches reported after en dovascular procedures are usually very acute [32], they may show similar mechanisms as post-CAD headache: mechanical stimulation of the arterial wall (stretching, distorsion), local inflammatory changes and vasodilata tion in collaterals. Olesen et al [33] suggested that throm boembolic ischemia may also trigger an attack of migraine in migraine patients and also in nonmigraine patients; they suggested that such acute episodes may be due to the effect of a borderline perfusion which lowers the threshold for developing migraine aura with or without headache [33]: this mechanism is unlikely in our patients, because none of them had an aura.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16] This dilation can be induced by mechanical forces as well as chemicals. It is well known that many patients experience a headache during angioplasty of the intracranial artery, 7,8,13 and a similar mechanism may apply to headache development after coil embolization. During and after coiling, if coil packing is enough to entrap blood and to not permit free blood flow, thrombosis can be induced in the coil frame and aneurysmal sac.…”
Section: Discussionmentioning
confidence: 99%